2009
DOI: 10.1074/jbc.r800050200
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation and De-SUMOylation: Wrestling with Life's Processes

Abstract: The small ubiquitin-like modifier (SUMO) is a ubiquitinlike protein that covalently modifies a large number of cellular proteins. SUMO modification has emerged as an important regulatory mechanism for protein function and localization. SUMOylation is a dynamic process that is mediated by activating (E1), conjugating (E2), and ligating (E3) enzymes and readily reversed by a family of ubiquitin-like protein-specific proteases (Ulp) in yeast and sentrin/SUMO-specific proteases (SENP) in human. This review will fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
408
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(411 citation statements)
references
References 50 publications
(35 reference statements)
2
408
0
1
Order By: Relevance
“…S mall ubiquitin-related modifier (SUMO) proteins can be conjugated onto specific lysine residues of a wide variety of proteins, creating branched peptides 1,2 . Proteinconjugated SUMO binds SUMO-interacting motifs, inducing conformational changes and stabilizing intra-or intermolecular interactions 3 .…”
mentioning
confidence: 99%
“…S mall ubiquitin-related modifier (SUMO) proteins can be conjugated onto specific lysine residues of a wide variety of proteins, creating branched peptides 1,2 . Proteinconjugated SUMO binds SUMO-interacting motifs, inducing conformational changes and stabilizing intra-or intermolecular interactions 3 .…”
mentioning
confidence: 99%
“…It can be reversed by a family of Sentrin/SUMO-specific proteases (SENPs) (Hay, 2007;Yeh, 2009). Mounting evidence demonstrates that SENP family members play crucial roles in determining the protein SUMOylation status and activity (Cheng et al, 2007;Hay, 2007;Yeh, 2009). We previously reported that SENP1 is involved in hypoxia signaling, angiogenesis, T and B cell development, and mitochondrial biogenesis via de-SUMOylation of distinct targets (Cheng et al, 2007;Cai et al, 2012;Van Nguyen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…SUMOylation is catalyzed by activating enzyme (E1), conjugating enzyme (E2), as well as ligating enzyme (E3). It can be reversed by a family of Sentrin/SUMO-specific proteases (SENPs) (Hay, 2007;Yeh, 2009). Mounting evidence demonstrates that SENP family members play crucial roles in determining the protein SUMOylation status and activity (Cheng et al, 2007;Hay, 2007;Yeh, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…SUMO modification has now emerged as an important regulatory mechanism in many signaling pathways through alteration of the function of target proteins (9,11,12). SUMOylation is catalyzed by activating (E1), conjugating (E2), and ligating (E3) enzymes.…”
mentioning
confidence: 99%
“…SUMO (also called Sentrin) is a novel ubiquitin-like protein that can covalently modify a large number of proteins (9,10). SUMO modification has now emerged as an important regulatory mechanism in many signaling pathways through alteration of the function of target proteins (9,11,12).…”
mentioning
confidence: 99%